Micro/Nanosilver Contribution in Modifying the Lubrication Film to Improve Friction and Wear Behaviors of TiAl-10 wt.%Ag Composite - Kang Yang; Na Xiao (Advances in Materials Science and Engineering)
Tribological performances of solid films are studied to improve their application range while retaining the longevity and high accuracy of TiAl alloy. For a ball-on-flat tribopair system, addition of micro/nanosilver improved the tribological behaviors of TiAl-10 wt.% Ag self-lubricating composite (TASC), compared to those of TiAl alloy. Notably, during microstructure evolution of the wear scar cross-section, a large amount of silver migrated from the TASC to the wear scar, and the silver distributions increased. This influx continuously enriched silver on the wear scar cross-section and formed a low-hardness lubrication film. Concurrently, a large amount of wear debris from the dry sliding wear contributed enough refinements to form a high hardness grain refinement layer. The results confirmed the formation of a 0.75 GPa hardness film with solid lubrication on a grain refined layer of 6.86 GPa hardness, resulting in excellent antifriction and wear resistance from 72 min to 90 min of the TASC. These results can help to evaluate the tribological characteristics for their commercial application and can conceptualize possible solutions for TiAl alloy-base components.